[Rezension von: Stunt, Timothy C. F, The Life and Times of Samuel Prideaux Tregelles] - Mills, R. J. W. (The journal of ecclesiastical history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022046920001955/resource/name/firstPage-S0022046920001955a.jpg